Expressão do gene otimizado da proteína p26 do vírus da anemia infecciosa equina em Escherichia coli - FONTES, Karin Florencio Lins de Paiva (2013)
Equine Infectious Anemia (EIA), considered one of the most important viruses in horses in the world, is caused by a lentivirus of the Retroviridae family. It is a chronic infection without treatment, mainly prevalent in regions with hot and humid climate, favorable for transmission by blood-sucking insects. According to the Ministry of Agriculture, Livestock and Supply (MAPA), the restriction of transit and slaughter of infected animals are the strategies for the control of EIA in Brazil, which causes losses in equine breeding. The official diagnosis of the disease is carried out by detection of circulating antibodies by Agar Gel Immunodiffusion (AGID) and ELISA. The p26 protein from EIAV is highly conserved and used in most diagnostic tests, since it induces a strong humoral response. The aim of this work was the production of a p26 recombinant protein in Escherichia coli for use in serologic tests. The p26 gene sequence was optimized with respect to E. coli codon usage, in order to maximize protein production, and was added with a marker sequence of six histidine residues (6xHis-tag) for later protein detection and purification. The sequence was synthesized and cloned downstream of the gene of a maltose binding protein (MBP2*) on the pMAL-c4X expression vector. The E. coli gene induction was performed by Isopropyl β-D-1-thiogalactopyranoside and the resulting protein (MBP2*.p26mod) was detected by SDS-PAGE gel and Western blot with monoclonal anti-HIS. The MBP2*.p26mod was visualized as a 68.5 kDa band, the recombinant fusion protein was cleaved with factor Xa resulting in two bands of 42.5 and 26 KDa, corresponding to MBP2* and p26mod respectively. The MBP2*.p26mod purification was performed with affinity chromatography by nickel resin and yielded 78.12 mg/L of bacterial culture. The MBP2*.p26mod protein was intensely immunoreactive at AGID test where precipitation lines were observed only among the positive sera, including reference OIE serum, and the protein MBP2*.p26mod, showing high analytical sensitivity and specificity of the recombinant protein.